LECTIN BINDING PROFILE OF SKIN AND ITS DERIVATIVES FROM HUMAN FETUSES AFTER PRETERM DELIVERY 35-36 WEEKS OF GESTATION - Strus, Ch.I.; Yashchenko, A.M. (World of Medicine and Biology, 2012)
Skin samples from neck region of three male human fetuses after preterm delivery (35-36 weeks of gestation) were examined by a set of 7 lectins, including Con A, PNA, HPA, SBA, WGA, SNA and LABA. Probes under investigation resembled skin of adults, except for hair follicles, some of which demonstrated signs of immaturity. Due to detected significant redistribution of DMan, DGal, DGalNAc, DGlcNAc, NeuNAc and LFuc sugar determinants it was concluded that glycoconjugates play active role in histogenesis of skin and its derivatives, namely, during fibrillogenesis, biosynthesis and secretion of glands, formation of intercellular junctions and cornification processes of keratinocytes.
Keywords: fetal skin; lectin histochemistry